Comparison of Antibiotic Resistance and Virulence Factors among Escherichia coli Isolated from Conventional and Free-Range Poultry. (22nd October 2015) - Koga, Vanessa L.; Scandorieiro, Sara; Vespero, Eliana C.; Oba, Alexandre; de Brito, Benito G.; de Brito, Kelly C. T.; Nakazato, Gerson; Kobayashi, Renata K. T.
Abstract : Microbiological contamination in commercial poultry production has caused concerns for human health because of both the presence of pathogenic microorganisms and the increase in antimicrobial resistance in bacterial strains that can cause treatment failure of human infections. The aim of our study was to analyze the profile of antimicrobial resistance and virulence factors of E. coli isolates from chicken carcasses obtained from different farming systems (conventional and free-range poultry). A total of 156 E. coli strains were isolated and characterized for genes encoding virulence factors described in extraintestinal pathogenic E. coli (ExPEC). Antimicrobial susceptibility testing was performed for 15 antimicrobials, and strains were confirmed as extended spectrum of β -lactamases- (ESBLs-) producing E. coli by phenotypic and genotypic tests. The results indicated that strains from free-range poultry have fewer virulence factors than strains from conventional poultry. Strains from conventionally raised chickens had a higher frequency of antimicrobial resistance for all antibiotics tested and also exhibited genes encoding ESBL and AmpC, unlike free-range poultry isolates, which did not. Group 2 CTX-M and CIT were the most prevalent ESBL and AmpC genes, respectively. The farming systems of poultries can be related with the frequency of virulence factors and resistance to antimicrobials in bacteria.